Development of highly hydrophilic yolk-shell Fe3O4@C magnetic nanoparticles: a potential tool for the theranostics of cancer - Rodrigues, Raquel Oliveira (2017)
Due to their remarkable physicochemical properties acquired at the nanoscale, magnetic nanoparticles (MNPs) are of interest in several disciplines, such as data storage, water purification, biochips and biomedicine (1). In order to prevent the oxidation of the MNPs, and their aggregation, several procedures have been developed to encapsulate them as a magnetic core (2). In particular, carboncoated nanoparticles have several advantages in comparison to polymer or silica coatings, since they usually offer higher chemical and thermal stability, large surface area, biocompatibility and easier functionalization (1, 3). These properties are especially important for biomedical applications, where MNPs should be chemically-functionalized with specific biocompatible targeting molecules to allow their selective attachment to cells or tissues.